Development Model of Productive Islamic Endowment Fund (Waqf) Management at Walisongo Pecangaan Jepara Foundation - Moh Nasuka (Postgraduate Program, State Islamic University Prof. K.H. Saifuddin Zuhri Purwokerto, 2023)
Abstract Productive waqf is a waqf management scheme by producing waqf, so it is able to make benefit or sustainable income. But, development waqf in Indonesia is commonly doesn’t make any changes. Waqf is limited on religious activities such as mosque, musholla, school or graveyard establishment, so waqf in Indonesia doesn’t give any advantages economically. It is different with Walisongo Pecangaan Jepara Foundation which managing its waqf property productively. This study is aimed to describe the model of productive Islamic endowment fund in education institution and increasing people's economic empowerment. This study uses qualitative method with phenomenology approach. This study is supported by 2 data, premier data and secondary data. The obtained data then analyzed using data collection, data reduction, data display, drawing conclusion, and verification. The result of this study shows that waqf property in Walisongo Pecangaan Jepara Foundation has role in developing education institution, such as providing scholarship, providing welfare to educators and education staff, as establishment funding and maintenance of education facilities and infrastructure, as well as learning equipment funding. Beside, productive waqf of this foundation has role in community’s economic development, especially for rice field tenants and shop tenants in managing their business that can be used to fulfill their family needs. Keywords: Islamic Endowment Fund; Funding; Financial Management